Microphone Array Speech Processing. (16th September 2010) - Nordholm Nordholm, Sven Sven; Abhayapala Abhayapala, Thushara D. Thushara D.; Doclo Doclo, Simon Simon; Gannot Gannot, Sharon Sharon; Naylor Naylor, Patrick A. Patrick A.; Tashev Tashev, Ivan Ivan
Abstract :